Interoception and alcohol: Mechanisms, networks, and implications. (1st December 2021) - Lovelock, Dennis F.; Tyler, Ryan E.; Besheer, Joyce
Abstract: Interoception refers to the perception of the internal state of the body and is increasingly being recognized as an important factor in mental health disorders. Drugs of abuse produce powerful interoceptive states that are upstream of behaviors that drive and influence drug intake, and addiction pathology is impacted by interoceptive processes. The goal of the present review is to discuss interoceptive processes related to alcohol. We will cover physiological responses to alcohol, how interoceptive states can impact drinking, and the recruitment of brain networks as informed by clinical research. We also review the molecular and brain circuitry mechanisms of alcohol interoceptive effects as informed by preclinical studies. Finally, we will discuss emerging treatments with consideration of interoception processes. As our understanding of the role of interoception in drug and alcohol use grows, we suggest that the convergence of information provided by clinical and preclinical studies will be increasingly important. Given the complexity of interoceptive processing and the multitude of brain regions involved, an overarching network-based framework can provide context for how focused manipulations modulate interoceptive processing as a whole. In turn, preclinical studies can systematically determine the roles of individual nodes and their molecular underpinnings in a given network, potentially suggesting new therapeutic targets and directions. As interoceptive processing drives and influences motivation, emotion, and subsequent behavior, consideration of interoception is important for our understanding of processes that drive ongoing drinking and relapse. This article is part of the special Issue on 'Neurocircuitry Modulating Drug and Alcohol Abuse'. Highlights: Interoception is a critical contributor to alcohol use disorder. Alcohol alters peripheral interoceptive information and abilities. Interoception underlies motivated behavior. The insular cortex and salience network are important neural underpinnings. Drug discrimination tasks are powerful tools for exploring interoceptive mechanisms.